The Connotation and Construction Path of the Principle of Good Faith from the Perspective of Civil and Commercial Law. (2nd September 2022) - Ma, Li
Abstract : In order to explore the connotation and construction path of the principle of good faith from the perspective of civil and commercial law, this paper combines intelligent algorithms to analyze the connotation and construction path of the principle of good faith from the perspective of civil and commercial law. Moreover, this paper presents a topology network specially used to improve the energy absorption efficiency of the isolation resistor used in the power divider and theoretically analyzes the effectiveness of the isolation topology. In addition, this paper further optimizes the topology of the two-way broadband filter power divider and builds a simulation model based on the basic content of the principle of good faith. From the research results, the simulation model proposed in this paper can play a certain role in the connotation and construction path of the principle of good faith from the perspective of civil and commercial law. On this basis, some suggestions on the connotation and construction path of the principle of good faith are put forward.